Selection process of emerging technologies using AHP-FMCGP mixed method: transportation industry of Iran. (2019) - Bagherinejad, Jafar; Fakhrzad, Paria
Transportation industry is one of the most worth background that needs to be developed and updated every time, especially with respect to emerging technologies. In this paper, we developed a mathematical model including hybrid method of MCDM and GP to rank and prioritise the best transport emerging technologies in the field of intelligent transport systems (ITS) and nanotechnologies. This model has been designed by considering a hierarchical structure including three levels with five factors like technical, economical, market, environmental and culture at the first level; three areas like vehicle, road and human in the second level and four identified emerging technologies from Iran's transport industry at the third level under sub-section of vehicle. The selection processes including ranking and prioritising have been performed considering three main goals. For successful completion of our research, we used the hybrid method of AHP and FMCGP in the transportation industry of Iran. Here, our proposed three-level model concentrated on future use of emerging technologies in the transportation system of Iran. After solving the proposed hybrid model, sleepy-driver sensors technology was the final priority. The findings can also lead to effective decision makings on investment on future emerging technologies in transportation system of Iran.